Calibration of bronchial methacholine challenge: addressing dose accuracy and practicality - Flemming Madsen; Birgitte Hanel; Jann Mortensen (European Clinical Respiratory Journal)
Methacholine bronchial provocation (BMP) is a valuable tool in supporting the diagnosis of asthma, but the BMP must be validated regarding dosing, since the BMP basically is a dose response study.Historically, the dose delivered by a nebulizer has been calibrated gravimetrically, by weighing the nebulizer before and after dosing. However, this method is no longer recommended, since it has been recognized that a large fraction of the weight loss was due to evaporation. Unfortunately, practical alternatives are not available, forcing clinicians to rely on the manufacturer's specified dose output. We studied the validity of the dose claimed to be delivered by the Vyaire APS-Pro.Methods To determine the dose output, we applied a radioactive method, considered the gold standard, and we validated a commercially available chemical analysis of chloride.Results The output from the APS-Pro was found to be highly correlated (R2 = 0.94) with the dose specified by the APS-Pro software but was consistently 1.8 times higher. The new chemical method demonstrated accuracy comparable to the radiometric approach. Notably, we observed significant variations in output across different nebulizers.Discussion The methacholine dose delivered to the mouth via the APS-Pro does not align with company specifications due to variability between nebulizers and a non-linear relationship between nebulization time and output, leading to higher output rates during shorter nebulization periods.Conclusion Individual output calibration of specific BMP systems remains necessary, as current systems still do not consistently meet manufacturer’s specifications. Clinicians must therefore have access to practical calibration methods.